Bleeding risk assessment in hemophilia A carriers from Dakar, Senegal. Issue 8 (December 2017) - Seck, Moussa; Faye, Blaise F.; Sall, Abibatou; Sy, Diariétou; Touré, Sokhna A.; Dieng, Nata; Guéye, Youssou B.; Gadji, Macoura; Touré, Awa O.; Costa, Cathérine; Lasne, Dominique; Rothschild, Chantal; et al.
Abstract : N/A: Hemophilia A carriers have an abnormal X chromosome with a molecular abnormality of FVIII gene . These carriers, long considered to be free of bleeding risk, could have the same symptoms as mild hemophiliacs. This study aim to assess bleeding risk of hemophilia A carriers monitored at the Clinical Hematology Department of Dakar. This is a prospective study of a period of 6 months including 22 hemophilia A carriers aged between 8 and 48 years. Hemophilia carriers were recruited using the genealogical tree of hemophiliacs followed in the service. Their diagnosis was carried out by long range PCR and Sanger sequencing method searching the molecular abnormality responsible for hemophilia in their family. Bleeding risk was determined using a questionnaire consisting of different bleeding symptoms quoted from −1 to 4 according to the severity. Total of different values allow to determine the bleeding score which was pathological if it was greater than or equal to 1. Medium age was 22.5 years (8–48) (SD = 9.28). Four hemophilia A carriers (18.1%) presented bleeding symptoms and had a bleeding score at least 1 ( P  = 0.02). Menorrhagia was predominant (13.6%) followed by epistaxis (9%), gingivorrhagia (9%), and prolonged bleeding after tooth extraction (9%). Factor VIII level was lower in hemophilia carriers who presented bleeding (42 ± 8.61 UI/l) versus hemophilia carriers without bleeding (100 ± 50.95 UI/l) ( P  = 0.001). There was no significant correlation between bleeding occurrence and age ( P  = 0.81), activated patial thromboplastin time value ( P  = 0.97) and FVIII/Von Willebrand Factor ratio ( P  = 0.12). One in five hemophilia carriers presented bleeding and the questionnaire was effective to identify hemophilia carriers who had a risk of bleeding.